(untitled) (Research, Society and Development, 2021)
The consumption of the "fad" diet "Low Carb High fat High Protein" (LCHFHP) is increasingly frequent nowadays because it causes faster weight loss and consequent improvement in quality of life. This integrative review aims to identify the metabolic, clinical and nutritional implications related to the consumption of Low Carb High fat High Protein diets. The bibliographic research was carried out through searches in the electronic databases Pubmed Central and Elsevier, from 2006 to 2018, using the following descriptors: “carbohydrate; dietary carbohydrates; diet, low carbohydrate; diet, carbohydrate-restricted; ketosis; diabetes; active engine; obesity; cardiovascular disease; protein; physical activity.” Initially, 68,219 articles were found. Of these, 40 were pre-selected fulfilling the inclusion criteria. However, among these 40, 28 were within the study profile. Most studies, although demonstrating positive effects with the consumption of the LCHFHP diet, in the short term, in terms of weight loss, reduction in the percentage of body fat, improvement in insulin sensitivity and glycemic control and reduction in the use of medications, showed that these effects were not always attributed to the reduction of carbohydrates in the diet. In addition to these long-term benefits, there was an increase in serum levels of inflammatory biomarkers, in the extent of atherosclerosis and in cardiovascular morbidity and mortality. More studies were carried out, mainly over the long term and with a larger sample, in order to better investigate the benefits or risks arising from the consumption of these diets, as well as the mechanism of action, especially in the face of non-communicable chronic diseases.